Necessidades formativas de professores de ciências de escolas do campo: um estudo no semiárido piauiense (2017-2018) - Silva, Alexandre Leite dos Santos (2018)
The objective of this work was to analyze the training needs of the science teachers of rural schools from a county in semiarid region from Piauí, Brazil. In this respect, the thesis defended is that a critical analysis with a dialectical perspective can contribute to more comprehensively reveal the training needs of the science teachers of rural schools. The research is based on the paradigm of Countryside Education and the conception of a science teaching based on problematization, thematic approach, social practice and the valorization of rural space, work and culture. For the development of the research, data were collected through interviews, forms, questionnaires, direct observation records during school visits, traineeship reports and other documents. The subjects who contributed to the data were 11 field science teachers, 13 principals, three coordinators, three representatives of local and regional social movements, six educators and 119 students of Countryside Education Course with focus in Sciences of the Federal University of Piauí. The analysis of the data was performed through the exploration, analysis and evaluation stages. The results showed that the science teachers of the rural schools investigated need to take practical classes, new and interesting methodologies and teaching techniques, to know how to work interdisciplinarily, specific knowledge in the area of Sciences, to develop new attitudes, know how to do contextualized teaching and knowledge about Countryside Education. In addition, teachers also need awareness, to develop critical thinking and to promote transformation at school and rural community level.